Comparative study of the three Zingiber Officinale species - Siti Ernieyanti Hashim, 1989-; Hasnah Mohd. Sirat, supervisor; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011